Songs and stories of the minority peoples in Yunnan. (Peking : China Reconstructs, 1960)
Bibliotheek Camille Huysmans
Supplement "China Reconstructs", december 1960
Engels
Brochure
Keywords: legenden; folklore; liederen; China